Preliminary Study of Determination of Classroom Lighting Performance and Led Luminaire Application Energy Saving Potential - Selimli, Selçuk; Bakar, Gözde; Aydemir, Erdoğan (Fırat University, 2020)
Evaluation of the lighting need in terms of comfort, health, safety and quality of life reveals the existence of a lighting system and need specific to different ambient conditions. The level of illumination of the training areas is determined within the scope of international standards. In addition to enlightenment, energy and its costs, which are among the important issues of today, are the subject of many research, development and application studies in order to meet the need for optimum lighting with minimum energy. Within the scope of this study, the illumination level provided by the existing tube fluorescent luminaire was measured in 10 classrooms in an educational institution and the illumination level was determined to be above 300 lux level specified in the standards. Although the lighting level is enough, it is evaluated that the required lighting level can be saved by changing the existing luminaires with led luminaires. With the change to be realized, 8161.56 kWh energy saving provision is determined as 3388.68 TL. It is considered that the existing luminaires can be replaced with an investment of 19500TL and the payback period is 5.75 years.

Aydınlatma ihtiyacının konfor, sağlık, güvenlik ve yaşam kalitesi açısından değerlendirilmesi farklı ortam koşullarına özel aydınlatma sistem ve ihtiyacının varlığını ortaya koymaktadır. Eğitim alanlarının da aydınlatılması düzeyi uluslararası standartlar kapsamında belirlenmiştir. Aydınlanma yanında günümüz önemli konuları arasında yer alan enerji ve maliyetleri, minimum enerji ile optimum aydınlatma ihtiyacının giderilmesi konusunda birçok araştırma geliştirme ve uygulama çalışmasının konusu durumundadır. Bu çalışma kapsamında bir eğitim kurumundaki 10 adet derslikte mevcut tüp floresan armatür ile sağlanan aydınlatma düzeyi ölçümlenmiş ve aydınlanma düzeyinin standartlarda belirtilen 300 lux düzeyinin üzerinde olduğu belirlenmiştir. Aydınlatma düzeyinin yeterli olmasına karşın gerekli aydınlatma düzeyinin mevcut armatürlerin led armatürlerle değişimi ile enerji tasarrufu sağlanabileceği değerlendirilmiştir. Gerçekleştirilecek değişim ile yıllık 8161,56 kWh enerji tasarrufu karşılığı 3388,68 TL olarak belirlenmiştir. 19500 TL tutarında yatırımla mevcut armatürlerin değişimi sağlanabilmesi ve geri ödeme süresinin 5,75 yıl olması değerlendirilmektedir.
Derslik Aydınlatma Performansının ve Led Armatür Uygulaması Enerji Tasarrufu Potansiyelinin Belirlenmesi Ön Çalışması